2014
DOI: 10.1007/s10126-014-9562-3
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Assessment by Microarray Analysis and Large-Scale Meta-analysis of the Metabolic Capacity of Cardiac and Skeletal Muscle Tissues to Cope With Reduced Nutrient Availability in Gilthead Sea Bream (Sparus aurata L.)

Abstract: The effects of nutrient availability on the transcriptome of cardiac and skeletal muscle tissues was assessed in juvenile gilthead sea bream fed with a standard diet at two feeding levels: i) full ration size and ii) 70% satiation followed by a finishing phase at the maintenance ration. Microarray analysis evidenced a characteristic transcriptomic profile for each muscle tissue following changes in oxidative capacity (heart > red skeletal muscle > white skeletal muscle). The transcriptome of heart and secondly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 85 publications
0
19
0
Order By: Relevance
“…It is also important to note that in both groups fed heat-treated SW diets the heart showed a more marked response than liver tissue in terms of the number of differentially expressed genes during recovery. This feature is not surprising, since sea bream cardiac muscle was previously reported in a microarray study to be the most responsive to nutrient restriction when compared with skeletal white and red muscle (Calduch-Giner et al, 2014). This probably reflects the high metabolic plasticity of heart as a tissue that must be highly regulated to maintain its essential functions.…”
Section: Discussionmentioning
confidence: 52%
“…It is also important to note that in both groups fed heat-treated SW diets the heart showed a more marked response than liver tissue in terms of the number of differentially expressed genes during recovery. This feature is not surprising, since sea bream cardiac muscle was previously reported in a microarray study to be the most responsive to nutrient restriction when compared with skeletal white and red muscle (Calduch-Giner et al, 2014). This probably reflects the high metabolic plasticity of heart as a tissue that must be highly regulated to maintain its essential functions.…”
Section: Discussionmentioning
confidence: 52%
“…Therefore, in order to obtain energy, amino acid oxidation had to increase in the exercised group, as reflected by the significant increase in mitochondrial CS activity. A meta-analysis of microarray gene expression profiling shows that mitochondria are among the first responders to nutritional and environmental stressors in gilthead sea bream (Calduch-Giner et al 2014). For instance, the gene expression of CS is up-regulated by thermal stress to cope with the enhanced oxidative capacity (Bermejo-Nogales et al 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Although comparisons across studies in different species is always difficult, transcriptome differences found between the two intestinal segments are of the same order than those found when comparing different organs and tissues, either in fish or other animal models. To put it in a proper perspective, the intestinal segment differences found in European sea bass are comparable to those found among heart and red and white skeletal muscle in gilthead sea bream, with more than 3000 DE genes (Calduch-Giner et al, 2014). Also, the level of DE probes among two different tissues in gene expression atlas of human and other model organisms is in the range of 50–90% (Son et al, 2005; Briggs et al, 2011; Freeman et al, 2012; Kapushesky et al, 2012).…”
Section: Discussionmentioning
confidence: 98%